2004
DOI: 10.1111/j.1395-3907.2004.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Dry eye syndrome in thyroid‐associated ophthalmo‐ pathy: lacrimal expression of TSH receptor suggests involvement of TSHR‐specific autoantibodies

Abstract: ABSTRACT.Purpose: We evaluated the relationship between ocular surface damage, elevated lid aperture/impaired Bell's phenomenon and reduced tear production in thyroidassociated ophthalmopathy (TAO). Suspecting a possible role of autoantibodies specific for TSH receptor (TSHR), we further investigated TSHR expression in the healthy lacrimal gland (LG). . We firstly demonstrate that lacrimal acinar cells physiologically express TSHR. Conclusions: As ocular surface damage in TAO significantly correlates with redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
114
1
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 23 publications
(22 reference statements)
12
114
1
11
Order By: Relevance
“…In addition, the evidence that lacrimal acinar cells physiologically express TSH receptor might indicate a role for thyroid hormone in lacrimal gland function. Furthermore, in thyroid-associated ophthalmopathy, a disease with high levels of autoantibodies against TSH receptor, the ocular surface damage was correlated with reduced tear secretion and not with other ocular signs of ophthalmopathy [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the evidence that lacrimal acinar cells physiologically express TSH receptor might indicate a role for thyroid hormone in lacrimal gland function. Furthermore, in thyroid-associated ophthalmopathy, a disease with high levels of autoantibodies against TSH receptor, the ocular surface damage was correlated with reduced tear secretion and not with other ocular signs of ophthalmopathy [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological, clinical, and experimental data showed a reduction of Schirmer test values and an alteration of impression cytology findings [30] . It was also shown that reduced levels of acetylcholine in the lacrimal gland of hypothyroid animals may contribute to the reduced tear secretion occurring in this condition [31] .…”
Section: Discussionmentioning
confidence: 99%
“…The lacrimal gland physiologically expresses the TSH receptor, which, in active GO, can bind with circulating anti-TSHR autoantibodies and contribute to lacrimal gland impairment [46]. This is an immune-mediated lacrimal gland dysfunction initially characterized by inflammation and followed by gland fibrosis and dropout, manifesting as a secondary Sjögren's syndrome in long-lasting disease [46,47,48,49,50]. Proteomics of tear fluids demonstrated an upregulation of inflammatory proteins and a downregulation of protective proteins in GO, with a significantly different panel compared to dry-eye patients and controls [51].…”
Section: Recommendationsmentioning
confidence: 99%
“…This proved that ocular inflammation is also responsible for the development of dry eye syndrome, which is independent of the degree of proptosis (21). The majority of the studies pertaining to dry eye syndrome and TAO have been conducted with Graves patients (7,9,11,12) and it has been seen that the studies on Hashimoto thyroiditis are rather limited (12,15). Previous experiments have shown that chronic deficiency of thyroid hormones causes ocular surface abnormalities and dry eye syndrome (10).…”
Section: Discussionmentioning
confidence: 99%
“…This relation may be explained by the fact that most of the effects of thyroid hormones on peripheral receptors are mediated by fT3 levels (16). The etiopathogenesis of dry eye syndrome related with TAO have been investigated in several recent studies (7,(9)(10)(11)(12). One of the main factors is an increase in tear film evaporation due to proptosis which subsequently causes tear hyperosmolarity and a decreased TBUT (17,18).…”
Section: Discussionmentioning
confidence: 99%